2005
DOI: 10.2165/00003088-200544010-00002
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age and Sex on the Clearance of Cytochrome P450 3A Substrates

Abstract: Cytochrome P450s (CYPs) are an important family of enzymes in the metabolism of many therapeutic agents and endogenous metabolic reactions. The CYP3A subfamily is especially prominent in these metabolic activities. This review article focuses on how the factors of age and sex may influence the in vivo activity of human CYP3A. The functional activity of CYP3A varies based on issues such as interaction with one or more substrates and between individuals and/or localisation. For CYP3A substrates, intrinsic cleara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
180
1
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(202 citation statements)
references
References 170 publications
11
180
1
10
Order By: Relevance
“…1), which is consistent with previous studies using CYP3A substrates or markers (Horsmans et al, 1992;Harris et al, 1995;Inagaki et al, 2002;Zhu et al, 2003;Cotreau et al, 2005;Lutz et al, 2010); however, we found no statistically significant sex-related difference (P = 0.37). The presence of the female sex steroids estrogen and progesterone in vivo may play a role in the modulation of this sex-related difference.…”
Section: Discussionsupporting
confidence: 92%
“…1), which is consistent with previous studies using CYP3A substrates or markers (Horsmans et al, 1992;Harris et al, 1995;Inagaki et al, 2002;Zhu et al, 2003;Cotreau et al, 2005;Lutz et al, 2010); however, we found no statistically significant sex-related difference (P = 0.37). The presence of the female sex steroids estrogen and progesterone in vivo may play a role in the modulation of this sex-related difference.…”
Section: Discussionsupporting
confidence: 92%
“…45 In men aged X65 years, the AUC of sildenafil was about twice as high and mean C max values about 60-70% higher than in younger men. 34,35 For vardenafil, the AUC and C max are increased by 52 and 34%, respectively, in elderly men.…”
Section: Pde5 Inhibitors In Special Populationsmentioning
confidence: 86%
“…MDZ is rapidly and extensively metabolized by the liver and intestinal microsomal enzymes (Heizmann and Ziegler, 1981;Kronbach et al, 1989). Many factors, such as age and sex (Hunt et al, 1992;Gibbs and Hosea, 2003;Wojnowski, 2004;Cotreau et al, 2005), concomitant medication (von Moltke et al, 1996), and hepatic function (Gibbs and Hosea, 2003), may influence the activity of CYP3A isoforms.…”
Section: Introductionmentioning
confidence: 99%